The impact of distress disclosure and anxiety on the association between social support and quality of life among Chinese women with systemic lupus erythematosus - Gao, Rui-Chen; Wu, Li; Shi, Pei-Li; Sang, Ni; Hao, Min; Wu, Guo-Cui (Frontiers in Psychiatry, 2022)
Studies have shown that social support and anxiety are related to the quality of life of female patients with systemic lupus erythematosus (SLE), but it is not clear how to affect the quality of life, and there are few studies on distress disclosure in patients with SLE, the impact on the quality of life is not clear. The purpose of this study was to explore the impacts of distress disclosure and anxiety on the association between social support and quality of life among Chinese women with SLE. A cross-sectional study was conducted, 237 samples were obtained. Measures included demographic characteristics, Lupus Quality of Life (LupusQoL), social support rate scale (SSRS), distress disclosure index (DDI), self-rating anxiety scale (SAS). Descriptive statistics, correlation analysis and moderated mediating effect analysis were carried out. The LupusQoL was negatively correlated with age, systemic lupus erythematosus disease activity index (SLEDAI), DDI and SAS, and positively correlated with SSRS. SSRS had a positive predictive effect on the LupusQoL, while SLEDAI and DDI had the opposite effect. SAS had a negative predictive effect on the LupusQoL. There were interactive effects of SAS and DDI on LupusQoL. In the moderated mediation model, SAS played moderating effect in the role of DDI on LupusQoL, DDI of female patients with SLE played a partial mediator role, the mediation effect was 0.19, the mediation effect ratio was 33.3%. In conclusion, to pay attention to the QOL, we should consider the mediator role of distress disclosure and the moderating role of anxiety.